Compact CMOS LiT VCO achieving 198.6 dBc/Hz FoMA. Issue 3 (1st February 2018) - Kim, S.‐J.; Seo, D.‐I.; Kim, J.‐S.; Song, R.; Kim, B.‐S.
Abstract : A compact CMOS linear transconductance (LiT) voltage‐controlled oscillator (VCO) in 65 nm CMOS process is presented. The proposed LiT technique is realised using NP core without a choke inductor to reduce die area and avoid dual resonance problem. The measured output frequency of the proposed VCO shows 11.18–11.98 GHz and phase noise is −112.62 dBc/Hz at 1 MHz offset frequency. DC power consumption of the VCO core and the buffer is 5.86 and 6 mW, respectively. It achieves a high figure of merit normalised to the area of 198.6 dBc/Hz.